Vinyl acetate-n-propyl vinyl ether copolymer porous material and method for preparing the same
Patent Information
- Application Number
- CN202611209331.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-23
AI Technical Summary
现有多孔材料难以同时兼顾低密度、高孔隙率、低热导率、能够保持宏观块体完整且具有良好的压缩形变恢复能力、以及损伤后恢复的性能需求
上述制备方法在不引入额外化学交联剂的情况下,通过共聚组成、冻结方式、冷冻干燥条件共同协同控制孔结构。能够制备得到密度低、孔隙率高、热导率低、宏观块体完整、具有一定的压缩形变恢复能力同时具有热辅助界面重新结合能力的多孔材料,适合用作轻质隔热、缓冲或可修复多孔构件。解决了现有多孔材料难以同时兼顾低密度、高孔隙率、低热导率、保持宏观块体完整且具有良好的压缩形变恢复能力、以及损伤后恢复的性能需求的技术问题。
Smart Images

Figure CN122958757A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of porous material preparation technology, and particularly to vinyl acetate-n-propyl vinyl ether copolymer porous materials and their preparation methods. Background Technology
[0002] Aerogels and freeze-dried porous materials typically consist of a continuous solid framework and a high proportion of gaseous pores, exhibiting characteristics such as low density, high porosity, low thermal conductivity, and customizable structures. They can be used for thermal insulation, buffering, adsorption, and lightweight components. Existing polymer aerogel technologies mostly use polyvinyl alcohol, cellulose, polyimide, polyurethane, or cross-linked resins as the framework. To improve mechanical stability, chemical cross-linking agents, inorganic reinforcing phases, or complex post-processing are usually required. These approaches suffer from problems such as multiple reaction steps, cross-linking agent residue, high material brittleness, poor compression set recovery, difficulty in recovering from damage, and difficulty in balancing structural and thermal insulation performance. Supercritical drying further increases equipment, pressure safety, and scalability costs. Existing porous materials struggle to simultaneously achieve the required low density, high porosity, low thermal conductivity, macroscopic bulk integrity, good compression set recovery, and post-damage recovery performance. Summary of the Invention
[0003] In response to the problems raised in the background art, the purpose of this invention is to provide a method for preparing a porous material of vinyl acetate-n-propyl vinyl ether copolymer. This method can prepare a porous material with low density, high porosity, low thermal conductivity, intact macroscopic bulk, certain compression deformation recovery ability, and thermally assisted interface re-bonding ability. This solves the technical problem that existing porous materials are unable to simultaneously achieve low density, high porosity, low thermal conductivity, maintain macroscopic bulk integrity, have good compression deformation recovery ability, and recover performance after damage.
[0004] Another objective of this invention is to propose a porous material of vinyl acetate-n-propyl vinyl ether copolymer prepared by the above preparation method, which has low density, high porosity, low thermal conductivity, intact macroscopic bulk, certain compression deformation recovery ability, and thermally assisted interface recombination ability, and can achieve recovery after fracture damage.
[0005] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A method for preparing a porous material of vinyl acetate-n-propyl vinyl ether copolymer includes the following steps: Step S1, preparation of copolymer solution: Add vinyl acetate-n-propyl vinyl ether copolymer to tert-butanol and stir until a homogeneous solution is formed to obtain copolymer solution; The repeating structural unit of the vinyl acetate-n-propyl vinyl ether copolymer is composed of vinyl acetate structural units and n-propyl vinyl ether structural units; Based on the total molar number of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, the proportion of the vinyl acetate structural units is 87 mol% to 93 mol%, and the proportion of the n-propyl vinyl ether structural units is the balance. Step S2, Molding: The copolymer solution is added into the mold; Step S3, Freezing: Place the mold at a temperature of -30℃ to -18℃ and freeze for 12 to 48 hours to obtain a frozen sample; Step S4, Vacuum freeze-drying: The frozen sample is subjected to vacuum freeze-drying to obtain a porous material of vinyl acetate-n-propyl vinyl ether copolymer; The porous material of vinyl acetate-n-propyl vinyl ether copolymer is cut to obtain a first part and a second part. The first part and the second part have cross-sections at the cut points. The cross-sections of the first part and the second part are re-attached and treated at 50-70°C for 10-60 minutes. The cross-sections of the first part and the second part are then re-bonded.
[0006] To further clarify, based on the total molar number of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, the proportion of the vinyl acetate structural unit is 93 mol%, and the proportion of the n-propyl vinyl ether structural unit is the remainder.
[0007] To further clarify, the mass fraction of the vinyl acetate-n-propyl vinyl ether copolymer is 4-5%.
[0008] To further clarify, the mass fraction of the vinyl acetate-n-propyl vinyl ether copolymer in the copolymer solution is 4%.
[0009] To further clarify, in step S3, the freezing temperature is -24℃ and the freezing time is 24h.
[0010] To further explain, in step S4, the conditions for vacuum freeze drying are: freeze drying at -45℃ to -55℃ and an absolute pressure not exceeding 50Pa for 96 to 98 hours.
[0011] To further explain, in step S4, the conditions for vacuum freeze drying are: freeze drying at -50°C and an absolute pressure of 35 Pa for 96 hours.
[0012] To further explain, after re-attaching the cross-section of the first part with the cross-section of the second part, it is treated at 60°C for 30 minutes.
[0013] A vinyl acetate-n-propyl vinyl ether copolymer porous material is prepared using the aforementioned preparation method, wherein the apparent density of the vinyl acetate-n-propyl vinyl ether copolymer porous material is 70–220 mg / cm³. 3 It has a porosity of 80%–95% and a thermal conductivity of no more than 0.09 W / (m·K).
[0014] Furthermore, the apparent density of the vinyl acetate-n-propyl vinyl ether copolymer porous material is 90–130 mg / cm³. 3 It has a porosity of 88%–94% and a thermal conductivity of 0.06–0.08 W / (m·K).
[0015] Compared with the prior art, the embodiments of the present invention have the following beneficial effects: The above preparation method, without introducing additional chemical crosslinking agents, synergistically controls the pore structure through copolymerization composition, freezing method, and freeze-drying conditions. It can produce porous materials with low density, high porosity, low thermal conductivity, intact macroscopic bulk, and a certain degree of compressive deformation recovery capability, as well as thermally assisted interfacial recombination ability. These materials are suitable for use as lightweight thermal insulation, buffering, or repairable porous components. This method solves the technical problem of existing porous materials that struggle to simultaneously achieve low density, high porosity, low thermal conductivity, maintain macroscopic bulk integrity, possess good compressive deformation recovery capability, and meet the performance requirements for post-damage recovery. Attached Figure Description
[0016] Figure 1 These are scatter plots showing the apparent density-porosity and density-thermal conductivity relationships of samples from Examples 1, 2, 3, and Comparative Example 1. Figure 1 (a) in the figure is a scatter plot of apparent density-porosity for samples from Examples 1, 2, 3, and Comparative Example 1. Figure 1 (b) is a scatter plot of apparent density-thermal conductivity for samples from Examples 1, 2, 3 and Comparative Example 1.
[0017] Figure 2 This is a SEM image of the microstructure (1.00 k×, scale bar 50 μm). Figure 2 Image (a) in the image is a SEM image of the sample surface from Example 4. Figure 2 Image (b) is an SEM image of the cross-section of the sample from Example 4. Figure 2 (c) in the figure is the SEM morphology of the sample surface of Comparative Example 5. Figure 2 (d) in the figure is the SEM morphology of the cross section of the sample in Comparative Example 5.
[0018] Figure 3 This is a test diagram of thermally assisted interface damage recovery. Figure 3 Image (a) in the figure is a macroscopic interface diagram of the sample from Example 1 after being treated at 60°C for 30 min in a heat-assisted interface damage recovery test. Figure 3 (b) in the figure shows the state of the sample of Example 4 after being treated at 60°C for 30 minutes in the heat-assisted interface damage recovery test, held by tweezers. Detailed Implementation
[0019] A method for preparing a porous material of vinyl acetate-n-propyl vinyl ether copolymer includes the following steps: Step S1, preparation of copolymer solution: Add vinyl acetate-n-propyl vinyl ether copolymer to tert-butanol and stir until a homogeneous solution is formed to obtain copolymer solution; The repeating structural unit of the vinyl acetate-n-propyl vinyl ether copolymer is composed of vinyl acetate (VAc) structural units and n-propyl vinyl ether (PVE) structural units; Based on the total molar number of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, the proportion of the vinyl acetate structural units is 87 mol% to 93 mol%, and the proportion of the n-propyl vinyl ether structural units is the balance. Step S2, Molding: The copolymer solution is added into the mold; Step S3, Freezing: Place the mold at a temperature of -30℃ to -18℃ and freeze for 12 to 48 hours to obtain a frozen sample; Step S4, Vacuum freeze-drying: The frozen sample is subjected to vacuum freeze-drying to obtain a porous material of vinyl acetate-n-propyl vinyl ether copolymer; The porous material of vinyl acetate-n-propyl vinyl ether copolymer is cut to obtain a first part and a second part. The first part and the second part have cross-sections at the cut points. The cross-sections of the first part and the second part are re-attached and treated at 50-70°C for 10-60 minutes. The cross-sections of the first part and the second part are then re-bonded.
[0020] Polyvinyl acetate (PVAc) is a thermoplastic polymer with certain film-forming and adhesive properties. However, its homopolymer segments are relatively rigid, making it prone to brittle fracture, pore wall breakage, or irreversible collapse during freezing and freeze-drying. While simply reducing density can decrease solid-phase thermal conductivity, it may lead to insufficient skeletal continuity, excessively large pore sizes, or residual solvents. Therefore, low density and high porosity do not necessarily guarantee good mechanical stability and the lowest thermal conductivity. The preparation method of this invention uses vinyl acetate-n-propyl vinyl ether copolymer as the skeleton and tert-butanol as the pore-forming solvent. The porous material is prepared through molding, freezing, and vacuum freeze-drying processes, and has the following characteristics: (1) A porous framework of copolymer with a specific composition. In this invention, vinyl acetate-n-propyl vinyl ether copolymer P (VAc-co-PVE) is used as the porous material framework. The proportion of vinyl acetate structural units in the vinyl acetate-n-propyl vinyl ether copolymer is limited to 87 mol% to 93 mol%, and the proportion of n-propyl vinyl ether structural units is the balance. By introducing an appropriate amount of PVE flexible segments, the glass transition temperature, chain segment flexibility and interfacial diffusion ability are adjusted, and the molecular chain flexibility is improved. The pore walls dissipate some stress through chain segment conformation adjustment and slip, reducing irreversible brittle failure. This makes the vinyl acetate-n-propyl vinyl ether copolymer achieve a good balance between the framework support capacity and chain segment mobility. After freezing and vacuum freeze-drying, a vinyl acetate-n-propyl vinyl ether copolymer porous material with low density, high porosity and low thermal conductivity can be formed. It can not only maintain the integrity of the macroscopic block, but also has a certain compression deformation recovery ability.
[0021] (2) Slow freezing-vacuum freeze-drying process of tert-butanol solution: Using tert-butanol as the pore-forming solvent, a homogeneous solution of vinyl acetate-n-propyl vinyl ether copolymer is prepared, molded, and slowly frozen at -30℃ to -18℃ for 12 to 48 hours, followed by vacuum freeze-drying. Slow freezing allows sufficient growth time for tert-butanol crystals, resulting in larger, directional pores and continuous pore walls after sublimation during vacuum freeze-drying. This reduces the severe shrinkage and densification that occurs in rapidly frozen samples due to excessively thin pore walls. The process of this invention does not require supercritical drying or the addition of additional chemical crosslinking agents.
[0022] (3) The prepared vinyl acetate-n-propyl vinyl ether copolymer porous material can undergo interface damage recovery through heat assistance: When the vinyl acetate-n-propyl vinyl ether copolymer porous material is cut or broken, the fracture surface of the first part is re-adhered to the fracture surface of the second part, and treated at 50-70℃ for 10-60 min, the fracture surface of the first part and the fracture surface of the second part can form a macroscopically stable bond, which can be picked up as a whole and does not separate after light touch. This interface damage recovery process mainly relies on the cross-interface physical diffusion, re-entanglement and non-covalent interaction of chain segments, without involving new chemical cross-linking reactions, and belongs to heat-assisted physical interface reconstruction. Specifically, the cross-interface diffusion and re-entanglement are of the P (VAc-co-PVE) copolymer molecular chains. PVE structural units reduce the regularity of chain segment arrangement and increase chain segment flexibility, thus lowering the glass transition temperature. During heat-assisted treatment, chain segment movement near the fracture surface is enhanced, allowing the P(VAc-co-PVE) copolymer molecular chains to diffuse across the original fracture surface and re-entangle. The dipole interactions and van der Waals forces between ester and ether groups further form physical bonds. This process does not involve the creation of new chemical bonds or cross-linking reactions; it is a process of chain segment diffusion and reconnection between two macroscopic fracture surfaces. After the interface damage recovery treatment at the fracture surface, the porous structure of the porous material's main body is still retained.
[0023] (4) Comprehensive balance of structure, insulation, and recovery performance: This invention does not take the lowest density as the sole objective. Without introducing additional chemical crosslinking agents, the pore structure is controlled synergistically through copolymer composition, freezing method, and freeze-drying conditions. It can prepare porous materials with low density, high porosity, low thermal conductivity, intact macroscopic bulk, certain compression deformation recovery ability, and thermally assisted interface recombination ability, suitable for use as lightweight insulation, buffer, or repairable porous components. It solves the technical problem that existing porous materials cannot simultaneously achieve low density, high porosity, low thermal conductivity, maintain macroscopic bulk integrity, have good compression deformation recovery ability, and meet the performance requirements for post-damage recovery. The prepared vinyl acetate-n-propyl vinyl ether copolymer porous material can be used as a removable lightweight insulation liner in refrigeration equipment or a removable insulation filler for cryogenic pipelines, valves, and irregularly shaped equipment exteriors. In the above-mentioned application scenarios, the materials need to meet the requirements of being lightweight, heat-insulating, having complete assembly, and restoring their shape after being compressed. When the insulation pad suffers local damage such as cuts or breaks during assembly, disassembly, or transportation, heat treatment can be used to re-bond the damaged interface, thereby extending the service life of the material.
[0024] Preferably, based on the total number of moles of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, the proportion of the vinyl acetate structural unit is 93 mol%, and the proportion of the n-propyl vinyl ether structural unit is the remainder.
[0025] When the proportion of vinyl acetate structural units in the vinyl acetate-n-propyl vinyl ether copolymer is 93 mol% and the proportion of n-propyl vinyl ether structural units is 7 mol%, the prepared vinyl acetate-n-propyl vinyl ether copolymer porous material can achieve a better balance between the skeleton support capacity and the chain segment mobility. Compared with the porous material prepared by using vinyl acetate-n-propyl vinyl ether copolymer with a higher proportion of n-propyl vinyl ether structural units (the proportion of vinyl acetate structural units is 87 mol% and the proportion of n-propyl vinyl ether structural units is 13 mol%), it has the advantages of lower density, higher porosity and lower thermal conductivity.
[0026] To further clarify, the mass fraction of the vinyl acetate-n-propyl vinyl ether copolymer in the copolymer solution is 4-5%.
[0027] When the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer is too low, the prepared porous vinyl acetate-n-propyl vinyl ether copolymer will exhibit shrinkage, residual tert-butanol, or difficulty in complete molding, resulting in insufficient molding stability. Conversely, when the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer is too high, the porous vinyl acetate-n-propyl vinyl ether copolymer will have high density and shrinkage rate. Therefore, by optimizing the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer in the copolymer solution, the prepared porous vinyl acetate-n-propyl vinyl ether copolymer can balance complete molding, porosity, and thermal properties.
[0028] This invention obtains a fully formed porous block by synergistically adjusting the copolymer composition, copolymer solution concentration, freezing method, and freeze-drying conditions without introducing additional chemical crosslinking agents. The resulting porous material also possesses acceptable thermal insulation performance, compression set recovery ability, and heat-assisted interface damage recovery ability.
[0029] Preferably, the copolymer solution contains 4% vinyl acetate-n-propyl vinyl ether copolymer by mass.
[0030] To further explain, in step S2, the copolymer solution can be added to a centrifuge tube, a cylindrical mold, a plate mold, or other target component mold.
[0031] Preferably, in step S3, the freezing temperature is -24°C and the freezing time is 24 hours.
[0032] To further explain, in step S3, slow freezing is performed under ambient atmospheric pressure, and no additional pressure or vacuum is applied during the freezing stage.
[0033] To further explain, in step S4, the conditions for vacuum freeze drying are: freeze drying at -45℃ to -55℃ and an absolute pressure not exceeding 50Pa for 96 to 98 hours.
[0034] In step S4, the tert-butanol in the frozen sample sublimates under vacuum freeze-drying conditions, forming larger, directional channels and continuous pore walls, thus obtaining a vinyl acetate-n-propyl vinyl ether copolymer porous material.
[0035] To further explain, after vacuum freeze-drying in step S4, the freeze-dried sample can be ventilated, vacuumed, or dried at low temperature to reduce residual tert-butanol. It can also be cut or surface-encapsulated according to the needs of the application scenario.
[0036] Preferably, in step S4, the conditions for vacuum freeze-drying are: freeze-drying at -50°C and an absolute pressure of 35 Pa for 96 hours.
[0037] In a preferred embodiment, based on the total molar number of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, the proportion of vinyl acetate structural units is 93 mol%, and the proportion of n-propyl vinyl ether structural units is 7 mol%; the mass fraction of the vinyl acetate-n-propyl vinyl ether copolymer in the copolymer solution is 4%; in step S3, the freezing temperature is -24°C and the freezing time is 24 h; in step S4, the vacuum freeze-drying conditions are: freeze-drying at -50°C and an absolute pressure of 35 Pa for 96 h. The apparent density of the vinyl acetate-n-propyl vinyl ether copolymer porous material obtained in this preferred embodiment is 94.67–116.28 mg / cm³. 3 It has a porosity of 90.07%–92.0% and a thermal conductivity of 0.06921–0.0791 W / (m·K). It is a macroscopically intact block with a certain ability to recover from compression deformation, while retaining the ability to recombine at the thermally assisted interface.
[0038] Preferably, after the cross-section of the first part is re-attached to the cross-section of the second part, it is treated at 60°C for 30 minutes.
[0039] By bonding the damaged fracture surfaces together and treating them at 60°C for 30 minutes, the fracture surfaces can be recombined through chain segment diffusion and physical entanglement, resulting in good recovery performance after damage.
[0040] A vinyl acetate-n-propyl vinyl ether copolymer porous material is prepared using the aforementioned preparation method, wherein the apparent density of the vinyl acetate-n-propyl vinyl ether copolymer porous material is 70–220 mg / cm³. 3It has a porosity of 80%–95% and a thermal conductivity of no more than 0.09 W / (m·K).
[0041] The vinyl acetate-n-propyl vinyl ether copolymer porous material has low density, high porosity, low thermal conductivity, intact macroscopic bulk, and certain compression deformation recovery ability, as well as thermally assisted interface recombination ability, enabling recovery after cross-sectional damage.
[0042] Furthermore, the prepared vinyl acetate-n-propyl vinyl ether copolymer porous material is a white or milky white block, sheet or irregular shape, and has an open pore and / or semi-open pore structure.
[0043] Furthermore, the apparent density of the vinyl acetate-n-propyl vinyl ether copolymer porous material is 90–130 mg / cm³. 3 It has a porosity of 88%–94% and a thermal conductivity of 0.06–0.08 W / (m·K).
[0044] To facilitate understanding of the present invention, a more complete description is provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0045] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0046] In the following examples, both PVAc93 copolymer and PVAc87 copolymer refer to vinyl acetate-n-propyl vinyl ether copolymers. The repeating structural units of the vinyl acetate-n-propyl vinyl ether copolymer are composed of vinyl acetate (VAc) structural units and n-propyl vinyl ether (PVE) structural units, wherein: The PVAc93 copolymer (calculated based on the total molar number of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, with vinyl acetate structural units accounting for 93 mol% and n-propyl vinyl ether structural units accounting for 7 mol%) was prepared as follows: 34 g VAc, 6 g PVE, and 10 g methanol were added to a four-necked flask, stirred at 250 rpm, and nitrogen was bubbled through at 20 mL / min for 30 min, followed by heating to 60 °C. 0.4 g azobisisobutyronitrile (AIBN) was dissolved in 10 g methanol as an initiator solution. 3 mL of the initiator solution was added at once, nitrogen bubbling was stopped, and the valve was closed. The remaining initiator solution was then continuously added over 6 h. After the addition was complete, heating was stopped, and the mixture was allowed to cool naturally for 2 h. The reaction solution was poured into a glass petri dish and dried at 60 °C for 12 h to obtain a solid P (VAc-co-PVE) copolymer. NMR calculations showed that the VAc structural unit percentage was 93 mol%.
[0047] The PVAc87 copolymer (calculated based on the total molar number of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, with vinyl acetate structural units accounting for 87 mol% and n-propyl vinyl ether structural units accounting for 13 mol%) was prepared as follows: 30 g VAc, 10 g PVE, and 10 g methanol were added to a four-necked flask, stirred at 250 rpm, and nitrogen was bubbled through at 20 mL / min for 30 min, followed by heating to 60 °C. 0.4 g AIBN was dissolved in 10 g methanol as an initiator solution. 3 mL of the initiator solution was added at once, nitrogen bubbling was stopped, and the valve was closed. The remaining initiator solution was then continuously added over 6 h. After the addition was complete, heating was stopped, and the mixture was allowed to cool naturally for 2 h. The reaction solution was poured into a glass petri dish and dried at 60 °C for 12 h to obtain a solid P(VAc-co-PVE) copolymer. NMR calculations showed that the VAc structural unit percentage was 87 mol%.
[0048] The PVAc homopolymer (with vinyl acetate structural units comprising 100 mol%) was prepared as follows: 40 g of VAc and 10 g of methanol were added to a four-necked flask, stirred at 250 rpm, and nitrogen was bubbled through at 20 mL / min for 30 min, followed by heating to 60 °C. 0.4 g of AIBN was dissolved in 10 g of methanol as an initiator solution. 3 mL of the initiator solution was added at once, nitrogen bubbling was stopped, and the valve was closed. The remaining initiator solution was then continuously added over 6 h. After the addition was complete, heating was stopped, and the mixture was allowed to cool naturally for 2 h. 30 g of methanol was added for dilution, and the reaction solution was poured into a glass petri dish and dried at 60 °C for 12 h to obtain the solid PVAc homopolymer.
[0049] Example 1 (PVAc93-4wt%-slow-frozen-batch 1) A method for preparing a porous material of vinyl acetate-n-propyl vinyl ether copolymer includes the following steps: Step S1: Preparation of copolymer solution: Add 0.40g of PVAc93 copolymer to 9.60g of tert-butanol and stir until a homogeneous solution is formed to obtain the copolymer solution. The total mass of the copolymer solution is 10.00g, and the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer is 4wt%. Step S2, Molding: The copolymer solution is added into a cylindrical mold with an inner diameter of 1.3 cm; Step S3, Freezing: Place the mold at a temperature of -24℃ for 24 hours to freeze, and obtain a frozen sample; Step S4, Vacuum freeze-drying: Open the mold lid to ensure that the solvent can be removed during the freeze-drying process. Transfer the mold along with the frozen sample into a Christ Alpha 1-2 LDplus freeze dryer for vacuum freeze-drying, specifically freeze-drying at -50℃ and an absolute pressure of 35Pa for 96 hours. After demolding, a white, continuous blocky vinyl acetate-n-propyl vinyl ether copolymer porous material is obtained.
[0050] Example 2 (PVAc93-4wt%-slow-frozen-batch 2) Another batch of vinyl acetate-n-propyl vinyl ether copolymer porous material was prepared using the same preparation method as in Example 1.
[0051] Example 3 (PVAc87-4wt%-slow-freezing) Compared with Example 1, step S1 in Example 3 uses PVAc87 copolymer, while the remaining raw materials and preparation methods are the same as in Example 1, to obtain a vinyl acetate-n-propyl vinyl ether copolymer porous material.
[0052] Example 4 (PVAc93-5wt%-slow-freezing) Compared with Example 1, in step S1 of Example 4, 0.50g of PVAc93 copolymer was added to 9.50g of tert-butanol and stirred until a homogeneous solution was formed to obtain a copolymer solution. The total mass of the copolymer solution was 10.00g, and the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer was 5wt%. The remaining raw materials and preparation methods were the same as in Example 1, and a porous material of vinyl acetate-n-propyl vinyl ether copolymer was obtained.
[0053] Example 5 (PVAc87-5wt%-slow-freezing) Compared with Example 3, in step S1 of Example 5, 0.50g of PVAc87 copolymer was added to 9.50g of tert-butanol and stirred until a homogeneous solution was formed to obtain a copolymer solution. The total mass of the copolymer solution was 10.00g, and the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer was 5wt%. The remaining raw materials and preparation methods were the same as in Example 3, and a porous material of vinyl acetate-n-propyl vinyl ether copolymer was obtained.
[0054] Comparative Example 1 (PVAc-4wt%-slow-freezing) Compared with Example 1, Comparative Example 1 used PVAc homopolymer in step S1, while the remaining raw materials and preparation methods were the same as in Example 1, resulting in a porous material.
[0055] Comparative Example 2 (PVAc 93-4wt%-fast frozen) Compared with Example 1, in step S3 of Comparative Example 2, the mold was placed in liquid nitrogen for rapid freezing for 30 seconds, while the remaining raw materials and preparation methods were the same as in Example 1, resulting in a porous material.
[0056] Comparative Example 3 (PVAc93-3wt%-slow-frozen) Compared with Example 1, in step S1 of Comparative Example 3, 0.15g of PVAc93 copolymer was added to 4.85g of tert-butanol and stirred until a homogeneous solution was formed to obtain a copolymer solution. The total mass of the copolymer solution was 5.00g, and the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer was 3wt%. The remaining raw materials and preparation methods were the same as in Example 1, and a porous material was obtained.
[0057] Comparative Example 4 (PVAc 93-8wt%-slow-frozen) Compared with Example 1, in step S1 of Comparative Example 4, 0.80g of PVAc93 copolymer was added to 9.20g of tert-butanol and stirred until a homogeneous solution was formed to obtain a copolymer solution. The total mass of the copolymer solution was 10.00g, and the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer was 8wt%. The remaining raw materials and preparation methods were the same as in Example 1, and a porous material was obtained.
[0058] Comparative Example 5 (PVAc-5wt%-slow-frozen) Compared with Comparative Example 1, in step S1 of Comparative Example 5, 0.50 g of PVAc homopolymer was added to 9.50 g of tert-butanol and stirred until a homogeneous solution with a total mass of 10.00 g was formed. The mass fraction of PVAc homopolymer in the solution was 5 wt%. The remaining raw materials and preparation methods were the same as those in Comparative Example 1, and a porous material was obtained.
[0059] The following performance tests and analyses were performed on the samples obtained from the examples and comparative examples: 1. Apparent density, porosity, and thermal properties: (1) Test methods for apparent density and porosity: The sample mass m was measured using an electronic balance, and the dimensions were measured using vernier calipers. The apparent volume V was calculated based on geometric volume, and the apparent density ρ = m / V was calculated. The porosity P = (1-ρ / ρ0) × 100%, where ρ0 represents the skeletal density of the vinyl acetate-n-propyl vinyl ether copolymer matrix in a non-porous and dense state. In the porosity calculation, ρ0 = 1.17 g / cm³ was taken. 3 .
[0060] (2) Test method of thermal properties: Thermal conductivity and thermal diffusivity were tested using a Hot Disk TPS1000 thermal constant analyzer. A 7577 probe with a radius of 2.001 mm was used. The sample was clamped on both sides of the sensor to form a symmetrical structure. The typical test power was 5-10 mW, the test time was 10 s, and the test temperature was 25℃.
[0061] (3) Interface damage recovery performance test: Cut the sample into a first part and a second part, and re-attach the cross-section of the first part to the cross-section of the second part. Treat the sample in a 60℃ oven for 30 minutes and observe whether the treated sample can be stably bonded and picked up as a whole.
[0062] The apparent density, porosity, and thermal properties of the samples obtained in Examples 1, 2, 3, and Comparative Example 1 were tested, and the test results are as follows: Figure 1 As shown in Table 1.
[0063] Table 1. Test results of apparent density, porosity, and thermal properties. Both Examples 1 and 2 resulted in intact porous bulk materials with a porosity higher than 90%. The apparent density of the vinyl acetate-n-propyl vinyl ether copolymer porous materials obtained in Examples 1 and 2 ranged from 94.67 to 116.28 mg / cm³. 3 The porosity was 90.07%–92.00%, and the thermal conductivity was 0.06921–0.0791 W / (m·K), indicating that Examples 1 and 2 can form high-porosity bulk materials with the thermal insulation capabilities of lightweight porous materials. Furthermore, the thermal diffusivity of the sample from Example 1 was 0.2417 mm². 2 / s, the thermal diffusivity of the sample in Example 2 was 0.361 mm. 2 / s, the thermal diffusivity reflects the propagation rate of temperature disturbances within the material. A higher value indicates a faster transient thermal diffusion rate under the corresponding test conditions. Compared to Example 1, Example 2 exhibits both higher apparent density and thermal conductivity, as well as lower porosity, indicating that the solid-phase skeleton heat transfer path of the sample in Example 2 is relatively continuous between the two batches prepared using the same method.
[0064] The apparent density of the sample obtained in Example 3 was 203.00 mg / cm³. 3 The porosity was 82.90% and the thermal conductivity was 0.08332 W / (m·K). Compared with the samples of Examples 1 and 2, the samples of Example 3 had increased density, decreased porosity and increased thermal conductivity because the content of n-propyl vinyl ether structural units in the vinyl acetate-n-propyl vinyl ether copolymer was increased, the skeleton was softer, and it was easier to shrink and densify during freeze drying.
[0065] The samples from Examples 1, 2, and Comparative Example 1 were tested for interface damage recovery performance. After the cross-sections of the samples from Examples 1 and 2 were treated in a 60°C oven for 30 minutes, the interface marks were significantly reduced, and the samples could be picked up as a whole and remained stable after gentle touch. The apparent density of the sample obtained in Comparative Example 1 was 87.65 mg / cm³. 3 The porosity was 92.63% and the thermal conductivity was 0.07160 W / (m·K). The thermal insulation data of the sample obtained in Comparative Example 1 was close to or slightly better than that of Example 1 and Example 2. However, when the interface damage recovery performance of the sample in Comparative Example 1 was tested, the cross-section of the sample only achieved moderate interface fusion after being treated at 60℃ for 30 min. The cross-sectional bonding effect of the sample in Comparative Example 1 was worse than that of the samples in Example 1 and Example 2, and the thermally assisted interface re-bonding ability was poor.
[0066] Figure 1 Scatter plots are used to present the relative positions of the measured values from Examples 1, 2, 3, and Comparative Example 1. Figure 1 It can be seen that Examples 1 and 2 have lower density, higher porosity and lower thermal conductivity than Example 3. The thermal properties of Examples 1 and 2 are similar to those of Comparative Example 1, but the thermally assisted interface re-bonding ability is better.
[0067] 2. Microstructure analysis: The surface and liquid nitrogen brittle fracture surface were observed using scanning electron microscopy (SEM), with a typical accelerating voltage of 5 kV and gold sputtering for 30-40 s. The surface and fracture surface SEM morphology of Example 4 (PVAc93-5wt%-slow-frozen) and Comparative Example 5 (PVAc-5wt%-slow-frozen) were observed. Figure 2 It can be seen that the slow-frozen sample of Example 4 has large, directional pores. The surface and cross-section of PVAc93 show a relatively continuous fibrous or sheet-like porous skeleton, forming a continuous porous network and interconnected pore walls. Comparative Example 5 shows lamellarization, localized compaction and brittle fracture characteristics. The cross-section of Comparative Example 5 is more prone to brittle fracture.
[0068] Furthermore, the SEM pore size ranges of Examples 4, 5, and Comparative Example 5 were observed. The slow freezing process in Examples 4, 5, and Comparative Example 5 was changed to a rapid freezing process (i.e., in step S3, the mold was placed in liquid nitrogen for rapid freezing for 30 s), and the SEM pore size ranges of the corresponding samples were observed, as shown in Table 2 below. Simultaneously, the pore size of Comparative Example 2 (PVAc93-4wt%-rapid freezing) and Example 1 (PVAc93-4wt%-slow freezing-batch 1) samples were observed. Rapid freezing in Comparative Example 2 caused the solvent to rapidly nucleate and form fine pores. It can be seen that compared to slow freezing, rapidly frozen samples have smaller pore sizes (the pore size is adjustable), but the pore walls are thinner and prone to shrinkage. Under these conditions, the density and shrinkage rate of rapidly frozen samples with the same composition can be significantly higher than those of slowly frozen samples. Slow freezing is more suitable for obtaining low-density, high-porosity intact blocks.
[0069] Table 2. SEM pore size range results for different samples 3. Analysis of the influence of the mass fraction of vinyl acetate-n-propyl vinyl ether copolymer in the copolymer solution: The molding conditions of the samples from Examples 1, 4, 3, and 4 were observed and are shown in Table 3 below. The molding stability of the 3 wt% sample was insufficient, the density and shrinkage of the 8 wt% sample were too high, and the 4 wt%-5 wt% sample was more conducive to balancing complete molding, porosity, and thermal properties.
[0070] Table 3. Molding conditions of different samples 4. Compression deformation recovery performance test: Samples from Example 5 and Comparative Example 5 were subjected to compressive strain of 40% or 60%, and after unloading, allowed to stand for 10 minutes. The ratio of the recovered height to the initial height was used as the height recovery rate after 10 minutes. The test results are shown in Table 4 below. The height recovery rate of the PVAc87 copolymer sample under both compressive strains was higher than that of the PVAc homopolymer, indicating that after introducing PVE structural units, the pore walls can dissipate some stress through chain segment conformation adjustment and slippage, thereby improving the compressive deformation recovery ability and reducing irreversible brittle failure. This invention uses vinyl acetate-n-propyl vinyl ether copolymer as a porous material skeleton, which can maintain the integrity of the macroscopic bulk and has a certain compressive deformation recovery ability.
[0071] Table 4 Test Results of Compression Deformation Recovery Performance 5. Thermally assisted interface damage recovery: After cutting and re-joining the samples, they were treated at room temperature and 60°C for 30 min each. Qualitative evaluation was conducted based on the degree of interface closure, the ability to be lifted as a whole under its own weight, and whether they separated again after gentle touch. The sample of Example 1 showed good interface closure after treatment at 60°C, could be lifted as a whole, and remained stable under gentle touch. However, after treatment at room temperature, it failed to bond stably, still exhibiting obvious interface gaps, and could not be lifted as a whole and separated after gentle touch. This indicates that heating significantly promotes chain segment diffusion and re-entanglement at the interface. Comparative Example 1 showed only moderate fusion at 60°C, and the cross-section of Comparative Example 1 failed to bond after 30 min treatment at room temperature. The comparison results of the treatment of Example 1 at room temperature and under heat assistance are shown in Table 5 below.
[0072] Table 5 Comparison of heat treatment results for heat-assisted interface damage recovery test of Sample 1 in Example 1 Figure 3 Image (a) shows the macroscopic interface of the sample from Example 1 after treatment at 60°C for 30 min in a heat-assisted interface damage recovery test. Figure 3 Image (b) shows the state of the sample from Example 4 after being treated at 60°C for 30 minutes in a heat-assisted interface damage recovery test, held by tweezers. It can be seen that after heat-assisted treatment, the cross-section of the sample from Example 1 can form a stable bond, and the sample from Example 4 can be held by tweezers and lifted as a whole, proving that the bonded sample can withstand its own weight. The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a porous material of vinyl acetate-n-propyl vinyl ether copolymer, characterized in that, Includes the following steps: Step S1, preparation of copolymer solution: Add vinyl acetate-n-propyl vinyl ether copolymer to tert-butanol and stir until a homogeneous solution is formed to obtain copolymer solution; The repeating structural unit of the vinyl acetate-n-propyl vinyl ether copolymer is composed of vinyl acetate structural units and n-propyl vinyl ether structural units; Based on the total molar number of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, the proportion of the vinyl acetate structural units is 87 mol% to 93 mol%, and the proportion of the n-propyl vinyl ether structural units is the balance. Step S2, Molding: The copolymer solution is added into the mold; Step S3, Freezing: Place the mold at a temperature of -30℃ to -18℃ and freeze for 12 to 48 hours to obtain a frozen sample; Step S4, Vacuum freeze-drying: The frozen sample is subjected to vacuum freeze-drying to obtain a porous material of vinyl acetate-n-propyl vinyl ether copolymer; The porous material of vinyl acetate-n-propyl vinyl ether copolymer is cut to obtain a first part and a second part. The first part and the second part have cross-sections at the cut points. The cross-sections of the first part and the second part are re-attached and treated at 50-70°C for 10-60 minutes. The cross-sections of the first part and the second part are then re-bonded.
2. The method for preparing the porous material of vinyl acetate-n-propyl vinyl ether copolymer according to claim 1, characterized in that, Based on the total number of moles of all structural units in the vinyl acetate-n-propyl vinyl ether copolymer, the proportion of the vinyl acetate structural unit is 93 mol%, and the proportion of the n-propyl vinyl ether structural unit is the balance.
3. The method for preparing the porous material of vinyl acetate-n-propyl vinyl ether copolymer according to claim 1, characterized in that, In the copolymer solution, the mass fraction of the vinyl acetate-n-propyl vinyl ether copolymer is 4-5%.
4. The method for preparing the porous material of vinyl acetate-n-propyl vinyl ether copolymer according to claim 3, characterized in that, In the copolymer solution, the mass fraction of the vinyl acetate-n-propyl vinyl ether copolymer is 4%.
5. The method for preparing the porous material of vinyl acetate-n-propyl vinyl ether copolymer according to claim 1, characterized in that, In step S3, the freezing temperature is -24℃ and the freezing time is 24h.
6. The method for preparing the porous material of vinyl acetate-n-propyl vinyl ether copolymer according to claim 1, characterized in that, In step S4, the conditions for vacuum freeze drying are: freeze drying at -45℃ to -55℃ and an absolute pressure not exceeding 50Pa for 96 to 98 hours.
7. The method for preparing the porous material of vinyl acetate-n-propyl vinyl ether copolymer according to claim 6, characterized in that, In step S4, the conditions for vacuum freeze drying are: freeze drying at -50℃ and an absolute pressure of 35Pa for 96 hours.
8. The method for preparing the porous material of vinyl acetate-n-propyl vinyl ether copolymer according to claim 1, characterized in that, After re-attaching the cross-section of the first part to the cross-section of the second part, it is treated at 60°C for 30 minutes.
9. A porous material of vinyl acetate-n-propyl vinyl ether copolymer, characterized in that, The vinyl acetate-n-propyl vinyl ether copolymer porous material prepared using the preparation method according to any one of claims 1 to 8 has an apparent density of 70 to 220 mg / cm³. 3 It has a porosity of 80%–95% and a thermal conductivity of no more than 0.09 W / (m·K).
10. The porous material of vinyl acetate-n-propyl vinyl ether copolymer according to claim 9, characterized in that, The apparent density of the vinyl acetate-n-propyl vinyl ether copolymer porous material is 90–130 mg / cm³. 3 It has a porosity of 88%–94% and a thermal conductivity of 0.06–0.08 W / (m·K).